ANALISIS TINGKAT KESEHATAN KOPERASI BERDASARKAN PERATURAN MENTERI KOPERASI DAN UKM NOMOR 9 TAHUN 2020 TENTANG PENGAWASAN KOPERASI PADA PRIMER KOPERASI MAJU SEJAHTERA SPN POLDA METRO JAYA - Lestari, Violita Eka; Afif, M. Nur; Aziz, Ayi Jamaludin (Komunitas Manajemen Kompetitif, 2025)
Cooperatives, a vital pillar in the Indonesian economy, are built on the principles of economic democracy. However, their development is not without challenges, including management, financial, and governance issues that can impact their sustainability and effectiveness. Therefore, an urgent need for an evaluation mechanism arises to ensure that cooperatives can operate healthily and contribute optimally to their members. Minister of Cooperatives and SMEs Regulation Number 9 of 2020 provides a method for assessing the health level of cooperatives, serving as a guide to objectively assess cooperative performance in governance, risk profile, financial performance, and capital. This research aims to analyze the Primary Cooperative Maju Sejahtera SPN Polda Metro Jaya's health level for 2018-2022 using a qualitative descriptive approach. The assessment is based on the concepts outlined in the Minister of Cooperatives and SMEs Regulation Number 9 of 2020. Moreover, Technical Guidelines Number 15 of 2021, supported by interviews and documentation methods. The results indicate that this cooperative has a governance score of 24.70, a risk profile score of 12.50, a financial performance score of 37.64, and a capital score of 15.00, all classified as healthy. The cooperative achieved a total score of 89.84, which is also classified as healthy.